Soap Operas and Artistic Legitimation: The Role of Critical Commentary. (25th March 2015) - Harrington, C. Lee; Scardaville, Melissa; Lippmann, Stephen; Bielby, Denise D.
Abstract: This article explores the artistic legitimation process of U.S. daytime soap operas through analysis of commentary published in The New York Times from 1930 to 2010. While soap operas gained economic legitimacy over time (due to profit-earning potential) and were popular with audiences, they were never widely classified as an "art" form. Through examination of 3 aspects of The New York Times articles—tone of critical commentary, viewership of critical commentary, and themes of critical commentary—we explore the role of evaluative press coverage in the validation, or lack thereof, of the soap opera form. Implications for the decline of the genre are also discussed .